Can Muslim Communities Empower through Ethnic-based? A Case Study in Indonesia - Dianidza Arodha; Maya Panorama; Moh. Syawaludin; Khairunnisa Musari (UIN Sunan Gunung Djati Bandung, 2025)
This study examines determinants and praxis of economic and social empowerment among Ethnics Muslim communities. It introduces the TENGKA model (Trust, Effort, Networking, Keeping, Active) as a culturally embedded framework for empowerment. Using an explanatory sequential mixed-methods design, the research identifies how physical capital, human capital, social capital, and the competence of empowerment actors shape empowerment outcomes. Empirical findings show that human capital, social capital, and actor competence significantly influence empowerment; local practices: aresan, sombhengan-bhelin, bhetonan, pesantren, madrasah, KOPWAN, lobenyu, posyandu, and PAMSIMAS, function as operational manifestations of social capital and Islamic-infused local wisdom. The paper advances the theoretical contribution by explicitly linking the TENGKA components to Islamic intellectual heritage (Qur'anic injunctions, Prophetic hadith, and classical and contemporary scholarship), and situates TENGKA alongside ACTORS and Ibn Khaldun’s ashabiyah to highlight complementarities and differences. We discuss transferability to other Muslim communities and propose practical implications for policy design and community-based interventions. The study contributes empirically and theoretically to scholarship on Islamic community empowerment and offers an operational model for culturally sensitive programs.